Effects of fine-scale pattern of dwarf bamboo on understory species diversity in abies faxoniana forest, South West, China - Yong-Jian Wang,; Xue-Ping Shi,; Yue, Peng; Zhang-Cheng Zhong,; Jian-Ping Tao, (Universiti Kebangsaan Malaysia, 2012)
Dwarf bamboo is recognized as a significant determinant of the structure and dynamics in temperate forests. Quantitative relationships between the abundance (density and coverage) of dwarf bamboo, Fargesia nitida, and micro-environments, species diversity on the floor were estimated in an Abies faxoniana pure forest in southwest China. Understory micro-environmental conditions (daily differences temperature and moisture, RPPFD under bamboo layer and ground cover) changed dramatically with the bamboo density. Stepwise multiple regression analyses indicated that abundance of F. nitida was mainly correlated with canopy characteristics and disturbance factors in the A. faxoniana pure forest. All richness indices decreased significantly with the bamboo density and RPPFD under bamboo layer. Importance values (IV) of understory species in different bamboo densities and Detrended canonical correspondence analysis (DCCA) indicated three understory plant groups, resistant to high bamboo abundance (Group A), resistant to intermediate bamboo abundance (Group B) and sensitive to bamboo abundance (Group C). These groups mainly responded to abundance of bamboo and RPPFD under bamboo layer, resulted from the integration of characteristics of bamboo, canopy and topography factors. Different bamboo abundance had different influences on understory species diversity and groups. Dense F. nitida condition (> 10 culms/m2) had significant negative effect and 0-5 bamboo condition had not significant negative effect on understory species diversity in A. faxoniana forest. We suggest the fine-scale analysis on effects of bamboo abundance should be taken account into considering in heterogeneous patches in process of the succession and regeneration of natural forests.